Relationship between the Mandibular Inferior Cortical Bone Thickness and The Second Cervical Vertebra Density in Women Relative to Menopause Using Cone-Beam Computed Tomography - Sepehri, Taraneh; Jafari-pozve, Nasim; Arianezhad, S. Marjan; Aryanezhad, Sasan (Journal of Dental School, 2024)
Objectives This study aimed to assess the correlation between the second cervical vertebra (C2) density and the mandibular inferior cortical bone thickness at the mental foramen in women before and after menopause on cone-beam computed tomography (CBCT) scan as a predictor of the risk of osteoporosis. Methods This retrospective cross-sectional study analyzed 176 CBCT scans from a sample of 88 post-menopausal women and 88 non-menopausal women. The thickness of the mandibular inferior cortical bone was assessed using cross-sectional CBCT images at the mental foramen, a measurement referred to as the mental index (MI), using the NNT viewer software. Additionally, the density of the C2 vertebra was measured on both coronal and axial CBCT sections. The collected data were then analyzed using various statistical tests, including the independent t-test, ANOVA, Tukey’s test, and Pearson’s correlation test, with a significance level set at α=0.05. Results No significant difference was found in the mean density of the C2 vertebra or the mean MI between menopausal and non-menopausal women. However, a significant correlation was found between the C2 density and MI in all women (r=0.445, P<0.001) and also in non-menopausal women (r=0.704, P<0.001); this correlation was more pronounced in younger age groups. Conclusion The present results showed that the C2 density and the mandibular inferior cortical bone thickness were not significantly different between menopausal and non-menopausal women. The C2 density had a significant correlation with the mandibular inferior cortical bone thickness in all women and also in non-menopausal women on CBCT images.